2011
DOI: 10.1371/journal.ppat.1001345
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Production Induced by Streptococcus pyogenes-Derived Nucleic Acids Is Required for Host Protection

Abstract: Streptococcus pyogenes is a Gram-positive human pathogen that is recognized by yet unknown pattern recognition receptors (PRRs). Engagement of these receptor molecules during infection with S. pyogenes, a largely extracellular bacterium with limited capacity for intracellular survival, causes innate immune cells to produce inflammatory mediators such as TNF, but also type I interferon (IFN). Here we show that signaling elicited by type I IFNs is required for successful defense of mice against lethal subcutaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
151
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(159 citation statements)
references
References 66 publications
(131 reference statements)
6
151
2
Order By: Relevance
“…Mancuso et al (30) reported that purified RNA derived from Streptococcus agalactiae (group B Streptococcus [GBS]) induced IFN-b in mouse mDCs in a TLR7-dependent manner. In contrast, Gratz et al (33) proposed that DOTAP-packaged lysates from Streptococcus pyogenes induced IFN-b by an RNA-dependent, but TLR7-independent, mechanism. Similarly, production of the classical NF-kB-dependent cytokines TNF and IL-1b upon bacterial RNA stimulation did not require TLR7-mediated signaling in murine BMDMs and mDCs (27,36), although these cells can be efficiently activated by TLR7 small molecule agonists, including imiquimod and R848.…”
Section: Tatjana Eigenbrod and Alexander H Dalpkementioning
confidence: 93%
See 2 more Smart Citations
“…Mancuso et al (30) reported that purified RNA derived from Streptococcus agalactiae (group B Streptococcus [GBS]) induced IFN-b in mouse mDCs in a TLR7-dependent manner. In contrast, Gratz et al (33) proposed that DOTAP-packaged lysates from Streptococcus pyogenes induced IFN-b by an RNA-dependent, but TLR7-independent, mechanism. Similarly, production of the classical NF-kB-dependent cytokines TNF and IL-1b upon bacterial RNA stimulation did not require TLR7-mediated signaling in murine BMDMs and mDCs (27,36), although these cells can be efficiently activated by TLR7 small molecule agonists, including imiquimod and R848.…”
Section: Tatjana Eigenbrod and Alexander H Dalpkementioning
confidence: 93%
“…Further analysis based on the transfection of RNase-or DNasetreated extracts of sonicated S. pyogenes demonstrated that bacterial RNA was critical for mounting IFN-b responses in murine mDCs, yet they were independent of TLR7. In contrast, S. pyogenes DNA was identified as an inducer of type I IFN in BMDMs (33). Together, these data raised the possibility that sensing of microbial RNA might be important for innate immune responses against S. pyogenes.…”
Section: Significance Of Bacterial Rna Recognition For Innate Immune mentioning
confidence: 96%
See 1 more Smart Citation
“…A further study using pDCs from IRF5-deficient mice, carrying or not carrying the DOCK2 mutation, confirmed that IRF5 had little effect on TLR9-stimulated IFNα secretion, but indicated an important role for IRF5 in the secretion of IFNβ (4). IRF5 was also required for the TLR9-stimulated production of IFNβ in the human pDC line CAL-1 (5) and for the production of IFNβ induced by streptococcal RNA in cDCs (6) and by the fungal pathogen Candida albicans in a pathway dependent on the Dectin 1 and Dectin 2 receptors (7). IRF5 was also found to be needed for the production of IFNβ by a small subset of viruses (8,9).…”
mentioning
confidence: 94%
“…Although the critical roles for bacterial DNA and viral RNA in the induction of innate immune responses have been acknowledged for long time, the importance of bRNA recognition has only recently started to be unraveled. It was demonstrated that intracellular delivery of bRNA induced secretion of type I IFNs, as well as proinflammatory cytokines, including TNF, IL-12p40, or IL-1b (10,(14)(15)(16)(17). In plasmacytoid DCs, bRNA-induced production of type I IFNs is mediated by TLR7 (15), whereas the murine receptor TLR13 was identified only recently to sense bRNA in both bone marrow-derived macrophages (BMDMs) and DCs by recognizing a unique nucleotide motif present in the bacterial 23S rRNA (18,19).…”
mentioning
confidence: 99%